The Effect of Benson Relaxation Technique on The Decrease Blood Pressure in Elderly Hypertension in The UPT Elderly Social Services of Pasuruan in Babat Lamongan - dyah pitaloka; hyan oktodia basuki (Jurnal Penelitian, 2019)
Introduction:Patient hipertension in the UPT Elderly Social Services of Pasuruan in Babat Lamongan is caused due to aging and stress which can increase sympathetic nervous system activity causing an increase in blood pressure. Benson relaxation can be used as an effort to cure hypertension because it contains self tranquilizers that can stabilize blood presure. The purpose of this study was to determine the effect of benson relaxation technique on the decrease blood pressure in elderly hypertension in the UPT Elderly Social Services of Pasuruan in Babat Lamongan. Methode: This study uses the  Pre Experiment design One Group Pre Post Test Designs conducted on 23 respondents. The sampling technique using systematic random sampling. The instruments used are Standart Operational Procedure and observation blood presure. Result: The research results showed that there was a effect of benson relaxation technique on the decrease blood pressure in elderly hypertension in the UPT Elderly Social Services of Pasuruan in Babat Lamongan. This is evidenced by the Wilcoxon test values obtainedρ = 0,002 (α ≤ 0,05). Solution: From the results of this study concluded benson relaxation can be used as an alternative to decrease blood pressure in elderly. Beside that the elderly must manage their diet.